Neuroendoscopy - Surgical instruments - Adrian Caceres (Brazilian Society for Pediatric Neurosurgery, 2021)
Objective: A thorough knowledge of the endoscope and associated hardware is essential to adequately apply neuroendoscopic techniques in the treatment of cerebral and spinal diseases. The purpose of this presentation is to discuss general principles regarding neuroendoscopy instruments and provide some useful tips for those initiating and/or delving deeper in the field. Methods: The development, evolution and correct use of endoscopic instruments are reviewed, as per the author's own wide experience and medical literature data. Results/Discussion: Both basic endoscopic surgical tools - lens systems, light sources, coagulation and recording devices, adapted scissors and forceps, etc. - along with advanced tools - holders, laser diodes, aspiration devices, arthropumps, etc. - were shown. Differences between rigid and flexible endoscopes were discussed, as well as specific features of the various current commercially available endoscopes (StorzÔ and BBraunÔ). Lastly, surgical aspects regarding positioning and neuroendoscopic approaches were also summarized. Conclusion: The field of neuroendoscopy is continually evolving. This basic knowledge of the neuroendoscopic tools is fundamental and must be combined with further technical refinements to achieve the best results in our clinical Pediatric Neurosurgery practice https://youtu.be/pvxAPjQGC08